The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00125-012-2559-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of the hypothalamic response to an oral glucose load

Abstract: Abbreviations ACTo the Editor: Functional MRI (fMRI) using a blood oxygen level dependent (BOLD) sequence provides a tool to measure the effects of alterations in blood glucose on the patterns and magnitudes of neuronal activation in the human brain [1]. Previous experiments using a glucose load have suggested that it is possible in humans to identify changes in the BOLD signal from areas within the hypothalamus [2-6]; however, the results have been contradictory. This study involved seven healthy participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…This is consistent with a study including lean adolescents (N = 14) that demonstrated no change in hypothalamic perfusion after glucose ingestion; however, the same study reported increased perfusion in adolescents with obesity (N = 24) . In agreement with the latter, an increase in hypothalamic BOLD signal after glucose ingestion has also been described in a study with adults with obesity and lean subjects (total N = 21), and two studies involving only normal‐weight adults (N = 18 and 7, respectively). Such discrepancies in prior findings of hypothalamic response to glucose ingestion may be due to distinct fMRI methodologies to evaluate the hypothalamic function (BOLD, cerebral blood perfusion, and temporal cluster analyses); variability due to the small samples in these and the current study, and to the fact that the glucose stimulus triggers a complex peripheral and CNS response orchestrated by the hypothalamus .…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with a study including lean adolescents (N = 14) that demonstrated no change in hypothalamic perfusion after glucose ingestion; however, the same study reported increased perfusion in adolescents with obesity (N = 24) . In agreement with the latter, an increase in hypothalamic BOLD signal after glucose ingestion has also been described in a study with adults with obesity and lean subjects (total N = 21), and two studies involving only normal‐weight adults (N = 18 and 7, respectively). Such discrepancies in prior findings of hypothalamic response to glucose ingestion may be due to distinct fMRI methodologies to evaluate the hypothalamic function (BOLD, cerebral blood perfusion, and temporal cluster analyses); variability due to the small samples in these and the current study, and to the fact that the glucose stimulus triggers a complex peripheral and CNS response orchestrated by the hypothalamus .…”
Section: Discussionsupporting
confidence: 86%
“…The hypothalamus plays a crucial role in food intake (Grill & Kaplan, ; Palkovits, ), and is extensively involved in homeostatic metabolic regulation (Carey et al ., ; Coll & Yeo, ; Zhou & Rui, ). Eating (Thomas et al ., ), and glucose (Matsuda et al ., ; Smeets et al ., , ; Flanagan et al ., ; Little et al ., ) or insulin administration (Kullmann et al ., ), exert significant suppressive effects on the blood oxygen level‐dependent (BOLD) signal within the hypothalamus. Additionally, the hypothalamus is physically connected to other areas involved in maintaining the homeostatic energy balance, and receives projections from the gastrointestinal tract via the brainstem (Blouet & Schwartz, ).…”
Section: Introductionmentioning
confidence: 98%
“…However, a brief summary is warranted given the intimate relationship between energy intake and glucose regulation. A decrease in neural activity following glucose and meal intake has been reported in the hypothalamus and elsewhere (Matsuda et al, 1999; Tataranni et al, 1999; Gautier et al, 2000; Liu et al, 2000; Smeets et al, 2005, 2007; Flanagan et al, 2012; Page et al, 2013) that differs in obesity and type 2 diabetes according to some studies (Matsuda et al, 1999; Gautier et al, 2000; Vidarsdottir et al, 2007). Moreover, studies employing task-based fMRI protocols have demonstrated activation of several CNS regions (in particular the orbitofrontal cortex, amygdala, hippocampus and insula) upon presenting the subject with visual food cues (LaBar et al, 2001; Killgore et al, 2003; St-Onge et al, 2005; Porubská et al, 2006; Führer et al, 2008) which was attenuated in the fed state in some studies (Baldo and Kelley, 2007; De Silva et al, 2011) and different in obesity or insulin resistance in others (Killgore and Yurgelun-Todd, 2005; Rothemund et al, 2007; Stoeckel et al, 2008; Martin et al, 2010; Wallner-Liebmann et al, 2010; Dimitropoulos et al, 2012; Heni et al, 2014a; Alsaadi and Van Vugt, 2015).…”
Section: Evidence From Studies In Humansmentioning
confidence: 89%